Impact of pharmacist-led educational intervention on predictors of diabetic foot at two different hospitals of Malaysia - Amer Hayat Khan; Muhammad Zahid Iqbal; Syed Azhar Syed Sulaiman; Aznita Ibrahim; Nor Shaffinaz Binti Yusoff Azmi; Muhammad Shahid Iqbal; Ahmed A Albassam (Wolters Kluwer Medknow Publications, 2021)
Objective: Diabetes mellitus (DM) is a chronic metabolic disorder that can initiate organ damage inside the body if not treated appropriately. Apart from tight glycemic control, a suitable educational intervention is also needed from health-care providers to stop or decrease the progression of organ damage in diabetic patients. This study intended to measure the impact of pharmacist-led educational intervention on improvement in predictors of diabetic foot in two different hospitals in Malaysia. Materials and Methods: In two tertiary care selected hospitals, the included diabetic patients were randomly divided into two study arms. In the control group, 200 patients who were receiving usual treatment from hospitals were included. However, in the intervention group, those 200 patients who were receiving usual treatment along with counseling sessions from pharmacists under the Diabetes Medication Therapy Adherence Clinic (DMTAC) program were included. The study continued for 1 year, and there were four follow-up visits for both study arms. A prevalidated data collection form was used to measure the improvement in predictors of diabetic foot in included patients. Data were analyzed by using the Statistical Package for the Social Sciences (SPSS) software program, version 24.0. Results: With the average decrease of 1.97% of HbA1c values in the control group and 3.43% in the intervention group, the univariate and multivariate analysis showed a statistically significant difference between both of the study arms in the improvement of predictors belonging to the diabetic foot (P < 0.05). The proportion of patients without any signs and symptoms of the diabetic foot in the intervention group was 91.7%, which increased from 42.3% at baseline (P < 0.05). However, this proportion in the control group was 76.9% at the fourth follow-up, from 48.3% at baseline (P < 0.05). Conclusion: A statistically significant reduction in the signs and symptoms of diabetic foot was observed in the intervention group at the end of 1 year. The progression of diabetic foot was significantly decreased in the pharmacist intervention group.